Kontribusi Wanita Tani Terhadap Pendapatan Rumah Tangga Buruh Tani Di Kecamatan Kawalu Kota Tasikmalaya - Nurdiansyah Nurdiansyah; Reny Hidayati; Dona Setia Umbara (Politeknik Kampar, 2023)
It appears that you provided a summary of a study conducted in Kawalu District, Tasikmalaya City, which aimed to determine the farmwork household income and women's contribution to farmworker household income. The study used a survey method with 32 respondents, employing simple random sampling. Based on the study results, the average household income of the 32 respondents was Rp2,858,831. The highest income recorded was Rp5,670,000, while the lowest was Rp1,000,000. The study found that women's contribution to the farmworker household income in Kawalu District, Tasikmalaya City, was approximately 27.83%. The information provided indicates the economic involvement of women in the farming sector and highlights their contribution to the overall household income. However, without access to the full study, it is challenging to interpret the context, limitations, and implications of these findings fully. If you have any specific questions or need further clarification, please feel free to ask.